Evaluation of wireless Ad Hoc Protocols using random motion - Imani, Nabil; Russed, Malik Asif (Computer Science and Engineering, BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.